Urinary tract infections in complicated kidney stones: Can they be correlated with Guy’s stone score? - Puia, Dragos; Radavoi, George Daniel; Proca, Tudor Marian; Puia, Ancuta; Jinga, Viorel; Pricop, Catalin (Journal of the Pakistan Medical Association, 2022)
Objective: To ascertain the existence of a connection between Guy’s stone score and infectious complications after percutaneous nephrolitholapaxy. Methods: The retrospective cohort, multi-centre study was conducted in the urology departments of Prof Dr Theodor Burghele Clinical Hospital and C.I. Parhon Clinical Hospital, Romania, and included data of patients who underwent percutaneous nephrolitholapaxy from January 1, 2017, to December 31, 2019. Based on urography, the subjects were assigned to four groups, from GSS1 to GSS4, in accordance with the Guy’s stone score classification. The complication rate after percutaneous nephrolitholapaxy was classified using the modified Clavien staging classification. Demographics, preoperative urine cultures, and the rate of complications were and compared. Data was analysed using SPSS 24. Results: Of the 246 patients, 116(47.2%) were males and 130(52.8%) were females. The overall mean age was 53.06±13.04 years (range: 18-83). The mean Guy’s stone score was 1.82±0.9. The rate of percutaneous nephrolitholapaxy success was 160(65.04%). There were 105(42.68%) patients in GSS1 group, 63(25.60%) in GSS2, 24(9.75%) in GSS3 and 54(21.95%) in GSS4. There were significantly more preoperative positive urine culture in GSS3 and GSS4 groups compared to GSS1 and GSS2 groups (p<0.05). The rates of complications were statistically different among the groups (p=0.019). Conclusion: Urinary tract infections were found more frequently in patients with higher Guy’s stone scores compared to those with low scores. The Guy’s stone score classification were found to be a useful tool in predicting the immediate success rate of percutaneous nephrolitholapaxy. Key Words: Kidney, Stones, Infection, PCNL.